Implementation of E-Government Policy from Governor Muhammad Zainul Madji (TGB) Era to Governor Zulkieflimansyah Era in West Nusa Tenggara Province - Zitri, Ilham; Rifaid, Rifaid; Lestanata, Yudhi (Universitas Muhammadiyah Ponorogo, 2023)
This article tries to explain the implementation of e-Government policies from Governor Muhammad Zainul Madji (TGB) era to Governor Zulkieflimansyah (Bang Zul). Four dimensions are measured to determine whether the implementation of e-government in the era of Muhammad Zainal Madji is well implemented, namely, the Policy, Institutional, Planning, and Application dimensions. In contrast, the Zulkieflimansyah era is measured by the Policy Domain, Governance Domain, and Service Domain. It uses a comparative descriptive method with a qualitative approach and using literature analysis. The results of the study show that the e-government policy of the NTB Province from the Muhammad Zainul Madji Era to the Zulkieflimansyah Era shows the results of